Abrupt fluctuations in North Pacific Intermediate Water modulated changes in deglacial atmospheric CO2 - Liu, Yanguang; Qiu, Yue; Li, Dongling; Artemova, Antonina V.; Zhang, Yuying; Bosin, Aleksandr A.; Gorbarenko, Sergey A.; Liu, Qingsong; Zhao, Debo; Sha, Longbin; Zhong, Yi (Frontiers in Marine Science, 2022)
As a major reservoir of heat and CO2, the Pacific Ocean is an important component of the global climate system, but the nature of its circulation under different climatic conditions remains poorly understood. We present sedimentary records of surface water hydrography and nutrient dynamics from the subarctic Pacific Ocean, with the aim of investigating changes in sea-ice coverage, biological productivity, and sea surface temperature in the subarctic Northwest Pacific since 32 kyr. Our records indicate an enhanced North Pacific surface water stratification from the last glacial to Heinrich Stadial 1, which generally limited the siliceous productivity supply to the surface water. A productivity peak during the Bølling/Allerød warm interval was associated with an increase in the atmospheric pCO2, and it was driven by the increased supply of nutrient- and CO2-rich waters. This process can be attributed to the collapse of the North Pacific Intermediate Water formation at the onset of the Bølling/Allerød interstadial. Moreover, a northward shift of the westerly winds and the gyre boundary could have modulated the expansion of the subpolar gyre, driving changes in poleward heat transport, biogeochemistry, and the hydroclimate of the North Pacific. Our results are consistent with modern evidence for a northward shift of the westerlies in response to global warming, which will likely result in CO2 outgassing from the subarctic Pacific Ocean in the future.